Negotiating risk: women responses to infant feeding issues in the Malaysian media - Emma Mirza Wati Mohamad,; Hasrul Hashim, (Faculty of Social Sciences & Humanities, UKM., 2011)
This paper explores Malay women’s responses to infant feeding issues in the media. It discusses three main events which are:(a) Melamine contamination in formula milk in China, (b) The risks of using Bisphenol-A baby bottles, and (c) Toxins in breast milk controversy. The paper seeks to understand the different ways women negotiate these infant feeding risks through their understanding of news/press reports while taking into consideration their own infant feeding experiences. It suggests that the media can influence people’s perception of risk. However, this often depends on the magnitude of risk portrayed by the media and mothers’ own understanding through personal experiences with breast/formula feeding.